2018
DOI: 10.1002/alr.22213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mometasone furoate–impregnated biodegradable nasal dressing on endoscopic appearance in healing process following endoscopic sinus surgery: a randomized, double‐blind, placebo‐controlled study

Abstract: Background Postoperative care is an important factor affecting the outcome of endoscopic sinus surgery (ESS) in patients with chronic rhinosinusitis (CRS). The aim of this study was to test the effect of mometasone furoate (MF)‐soaked biodegradable nasal dressings (BNDs) on endoscopic appearance in CRS patients with nasal polyps (CRSwNP) after ESS. Methods This study was a prospective, randomized, double‐blinded, placebo‐controlled study. A total of 64 CRSwNP patients with bilateral ESS were enrolled and rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 33 publications
1
42
2
Order By: Relevance
“…10,14 Furthermore, the differences in the durations of the included trials (1, 2, or 3 months) were a potential source of heterogeneity, and the follow-up time is extremely short. Finally, the types of bioabsorbable implants were different, including Gelfoam dressing (Pfizer, New York, NY), 18 NasoPore dressing (Stryker, Kalamazoo, MI), 16,17 calcium alginate dressing (Algi-Pack,Seoul), 21 SinuBand dressing (MedtronicXomed Inc., Jacksonville), 20 stents, 10,14 and Sinus-Foam spacer (Athrocare, Sunnyvale), 19 which may have led to heterogeneous results. To reinforce the validity of our meta-analysis, clinical trials of the same implant soaked in steroid following ESS as well as extended followup trials should be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14 Furthermore, the differences in the durations of the included trials (1, 2, or 3 months) were a potential source of heterogeneity, and the follow-up time is extremely short. Finally, the types of bioabsorbable implants were different, including Gelfoam dressing (Pfizer, New York, NY), 18 NasoPore dressing (Stryker, Kalamazoo, MI), 16,17 calcium alginate dressing (Algi-Pack,Seoul), 21 SinuBand dressing (MedtronicXomed Inc., Jacksonville), 20 stents, 10,14 and Sinus-Foam spacer (Athrocare, Sunnyvale), 19 which may have led to heterogeneous results. To reinforce the validity of our meta-analysis, clinical trials of the same implant soaked in steroid following ESS as well as extended followup trials should be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…14 Six studies were ruled out because the treatment was in-office; six studies were excluded because the dates were not available; and 13 studies were ruled out because the studies were not randomized controlled trials (RCTs). Ultimately, eight published articles were eligible for analysis, 10,14,[16][17][18][19][20][21] and the study reported by Adriaensen et al 20 was a three-arm study.…”
Section: Literature Searchmentioning
confidence: 99%
“…Two independent reviewers assessed the abstracts of the identified articles, excluding 1,067 of these records. Twenty-five full-text articles were assessed, with eight studies [18][19][20][21][22][23][24][25] having met eligibility criteria and thus were included in this review (Fig. 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…Finally, a randomized, double-blind, placebo-controlled trial was published in 2018 by Zhao et al 21 using a mometasone-impregnated NasoPore. Patients were randomized to receive first an 8-cm NasoPore, dosed with either 4 (1400 mg) or 8 (2800 mg) mL of mometasone, in one nasal cavity, and then a saline-impregnated NasoPore in the contralateral nasal cavity.…”
Section: Evidence On Clinical Outcomesmentioning
confidence: 99%